2014
DOI: 10.1016/j.ridd.2014.06.007
|View full text |Cite
|
Sign up to set email alerts
|

The impact of health checks for people with intellectual disabilities: An updated systematic review of evidence

Abstract: Health checks for people with intellectual disabilities have been recommended as one component of international health policy responses to the poorer health of people with intellectual disabilities. This review updates a previously published review summarising evidence on the impact of health checks on the health and well-being of people with intellectual disabilities. Electronic literature searches and email contacts were used to identify literature relevant to the impact of health checks for people with inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
120
0
14

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 95 publications
(140 citation statements)
references
References 56 publications
6
120
0
14
Order By: Relevance
“…The Learning Disabilities Observatory undertook a systematic review of the evidence base for annual health checks in 2011, 11 subsequently updated in 2014, 12 which summarised health gains and impacts from similar interventions both in the UK and internationally. The initial review identified 38 studies (45 in the later review) that comprised a total of > 5000 individuals receiving a health check.…”
Section: Evidence Base For Annual Health Checksmentioning
confidence: 99%
See 4 more Smart Citations
“…The Learning Disabilities Observatory undertook a systematic review of the evidence base for annual health checks in 2011, 11 subsequently updated in 2014, 12 which summarised health gains and impacts from similar interventions both in the UK and internationally. The initial review identified 38 studies (45 in the later review) that comprised a total of > 5000 individuals receiving a health check.…”
Section: Evidence Base For Annual Health Checksmentioning
confidence: 99%
“…These conclusions are also supported by the larger number of uncontrolled studies. 11,12 Evidence on health outcomes relating to health checks is far more limited and of poorer quality. Uncontrolled studies in the UK have reported a variety of benefits of health checks, including improved seizure control and weight management.…”
Section: Evidence Base For Annual Health Checksmentioning
confidence: 99%
See 3 more Smart Citations